Benarkah Suasana Toko dapat Mempengaruhi Pembelian Impulsif di MINISO Trans Studio Mall Bandung? - Aulya, Fathya Dwi (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Abstracts This study aims to evaluate the influence of store atmosphere on customers' impulse buying behaviour, specifically at MINISO at Trans Studio Mall Bandung. MINISO is a specialized retail store that offers a wide range of household and consumer goods, such as cosmetics, stationary, toys, and kitchenware. The study examines the impact of cleanliness, lighting and colour, and display or layout on cognitive behaviour. It involves a sample of 100 participants who visited MINISO, including both residents of Bandung and individuals from outside places. Correlation study indicates that cleanliness did not have a significant impact on cognitive behaviour. However, there were strong links observed between lighting and colour, as well as presentation or layout. The findings emphasize the significance of establishing an enjoyable retail environment to enhance customer happiness, yet these do not have a significant impact on stimulating impulsive purchasing behaviour.